Dampak Pandemi Covid-19 Terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor Di Provinsi Sulawesi Selatan (AT TAWAZUN: Jurnal Ekonomi Islam, 2021)
ABSTRAK - The purpose of this study was to determine the impact of Covid-19 on motor vehicle tax compliance in the province of South Sulawesi and government policies in overcoming this. At the end of 2019, precisely in December, the world was shocked by a phenomenon or event that was suspected to be a case of pneumonia whose etiology was unknown, where the case originated from the city of Wuhan, China which was called Covid-19. Motor Vehicle Tax (PKB) is a very large aspect of Regional Original Income (PAD). During Covid-19, many regions experienced a decrease in income in the tax sector, one example of the impact of Covid-19 in South Sulawesi. The method in this research is library research, interview and observation. The impact of Covid-19 has greatly weakened the state's economic condition and the state budget for both provincial and district revenues. The number of sectors affected by Covid-19, especially in compliance with the Mandatory PKB, which plays an important role in the provincial budget, various government policy efforts in dealing with various matters, so that the community continues to pay taxes.